Bar jako významné místo v migraci - Terry, Zuzana (Lidé města, 2022)
This paper presents the results of a six-month-long field research conducted in the capital of the Czech Republic in 2013. It is based on the research of a bar visited by Anglophone migrants. It aims to reveal how becoming a bar regular helped migrants to adapt to the new country and maintain their lives there. The studied group of migrants placed important practices into the space of the bar, through which they formed their meaning and memory in a new place, their new home. They domesticated the place to the extent that they had their own seats, glasses, and any newcomer, whether Czech or migrant, was observed and evaluated. The bar played the role of an intimate space; it was home-like and it was socially and materially changed by the migrants. The bar was a place where the migrants’ social bonds were performed and materialised. It was a place in the time and space of real physical contact within a migratory network.